Clinical Practice Patterns in Tic Disorders Among Movement Disorder Society Members. Issue 1 (28th October 2021) - Ganos, Christos; Sarva, Harini; Kurvits, Lille; Gilbert, Donald L.; Hartmann, Andreas; Worbe, Yulia; Mir, Pablo; Müller-Vahl, Kirsten R.; Münchau, Alexander; Shprecher, David; Singer, Harvey S.; Deeb, Wissam; et al.
Background: Tic disorders belong to the broad spectrum of pediatric and adult movement disorders. The wide variability in clinical presentations, applied assessment tools, and treatments are poorly understood. Objectives: To map practices and knowledge base of movement disorder clinicians concerning clinical features, pathophysiology, and treatment approaches in tic disorders. Methods: A 33-item survey was developed by the Tic Disorders and Tourette syndrome Study Group members of the Movement Disorder Society. The survey was distributed to the complete society membership and included responses from 346 members, 314 of whom reported treating tic disorders. Results: Approximately one third of survey respondents (35%) frequently evaluated patients with tics. The data revealed widespread use of existing guidelines (about 70%) and screening for comorbid disorders (>90%). The most common investigations used to rule out secondary causes of tics were imaging (92%), laboratory tests (66%) and neurophysiology (38%). Functional tics were the second most common tic etiology following primary tics. Only 27% of respondents reported confidence in knowledge about tic pathogenesis. Top rated interventions to treat tics were psychoeducation, cognitive behavioral intervention for tics (CBIT) and treatment for neuropsychiatric comorbidities. Antipsychotics were ranked as the most effective pharmacologic tic intervention. Conclusions: The majority of movement disorders specialists do not frequently encounter tics. There was sparse knowledge about tic pathophysiology. Psychoeducation, CBIT, the treatment of neuropsychiatric comorbidities and use of antipsychotics emerged as the most common interventions to treat tics. These results provide insight into what will be needed to improve the diagnosis and treatment of tic disorders.